The Impact of Foreign Direct Investment (FDI) and Domestic Direct Investment (DDI) on Gross Regional Domestic Product (GRDP) in Sumatra Island - Fitri Omita; Jean Elikal Marna (Jurnal Inovasi Pendidikan Ekonomi, 2026)
This study is motivated by persistent disparities in economic growth among the provinces of Sumatra, which are presumably linked to the unequal distribution of Foreign Direct Investment (FDI) and Domestic Direct Investment (DDI). Previous studies have yielded inconsistent results; some combined FDI and DDI into a single variable over a limited period, thereby preventing an analysis of the individual contribution and significance of each investment type. This study addresses this gap by examining the effects of FDI and DDI, both individually and simultaneously, on the regional Gross Domestic Product (GDP) of Sumatra between 2016 and 2025, testing Harrod-Domar and Keynesian investment theories in a regional context. This quantitative associative study utilises secondary panel data covering all 10 provinces of Sumatra from 2016 to 2025 (100 observations), obtained from the Indonesian Investment Coordinating Board (IAC) and the Central Statistics Agency (BPS). The data were analysed using panel data regression via the Random Effects Model (REM), selected based on Chow, Hausman, and Lagrange Multiplier tests. The results indicate that FDI does not have a significant effect on GDP (coefficient = 0.0011; probability = 0.9649), whereas DDI shows a positive and significant effect (coefficient = 0.1774; probability = 0.0000). When considered simultaneously, FDI and DDI have a positive and significant impact on regional GDP, with an F-statistic of 53.579 and an adjusted R-squared of 0.515; this suggests that, together, both variables explain 52.4% of the variation in regional GDP across Sumatra. By treating FDI and DID as distinct variables over an extended period and across provinces, this study clarifies the respective roles of each and highlights the need for policies that enhance FDI effectiveness while sustaining domestic investment growth.